Diagnostic Accuracy of Limited Protocol MRI for Diagnosis of Lumbar Disc Degeneration - Shaikh, Rabail Gul; Hussain, Munawar; Khan, Sohail Ahmed; Sattar, Amjad (Journal of Liaquat University of Medical & Health Sciences, 2021)
Objective: To determine the accuracy of limited protocol Magnetic resonance imaging of lumbar spine in determination of lumbar disc herniation, nerve root compression and annular tear taking findings of routine MRI as a reference standard. Methodology: A descriptive cross-sectional study was conducted from August 2016 to February 2017 at Dow Institute of Radiology (DIR), Dow University of Health Sciences (DUHS). All patients of either gender aged 20 years or more presenting for MRI with low back pain were included. Routine complete protocol included T1W spin echo (SE) images on the sagittal plane, fat suppression sequence on the sagittal plane and T2W fast spin echo (FSE) images on the sagittal and axial planes, while limited protocol included T2W fast spin echo images on the sagittal and axial planes. Statistical analysis for social sciences (SPSS version 24), Inc, USA was used for the purpose of statistical analysis. Results: The sensitivity and specificity of limited protocol of disc herniation, nerve root compression, and AT were found to be 100% taking full protocol for disc herniation, nerve root compression, and AT as a gold standard. A significant difference of disc herniation was observed with age (p-value: <0.001), gender (p-value: 0.011), NRC (p-value: <0.001), and AT (p-value: <0.001). Conclusion: Limited protocol MRI of lumbar spine can lead to a definite diagnosis of LDH, NRC and AT without causing any loss of information. Keywords: Low back pain, diagnostic accuracy, limited protocol MRI, disc herniation, nerve root compression